Customized surgical approach to small bowel perforation secondary to biliary stent migration: a case report and review of the literature - Hassanesfahani, Maryam; Brar, Karmen; Keating, Luke; Louis, Martine A.; Mandava, Nageswara (International Surgery Journal, 2024)
Endoscopic placement of a biliary stent to treat benign or malignant biliary obstructions is a well-established practice and may prevent the need for further surgical intervention. It can be associated with complications including occlusion, cholangitis, bleeding, as well as, late complications of migration and perforation. Stent migration and perforation, proximal or distal, are relatively uncommon with an overall incidence of 6 and 1% respectively. We reported a case of distal biliary plastic stent migration with delayed small bowel perforation which required surgical intervention.